Analysis of Earthquake Vulnerable Indicators in Exhausted Urban Tissue Case Study of Fakharan Neighborhood located in Kazerun County - Mohammadreza Ehsandoost; Ibrahim Zare (مهندسی و مدیریت ساخت)
Currently, many cities in the country are facing a problem called worn-out texture. These textures are the old core of cities and have become worn out and inefficient over time, or formed in modern times without observing the rules and regulations of architecture and urban planning. And so they are now facing a lot of problems and they are spreading to the whole city. It seems that in the worn texture, due to the wide range and intensity of the problems facing these tissues, the most efficient approach that can be used to deal with With the shortcomings and shortcomings, it is possible to achieve the goals of sustainable development in the field of improvement of these tissues. A conceptual model has been proposed to determine potential risks in a qualitative manner in Fakharan neighborhood, located in the east of Kazerun city. The results show that the passage of buildings and the destruction of buildings are in the range of risk severity, respectively. Potential for the study area.